Anticancer Potential of Watermelon Seed Extracts Against Lung and Breast Cancer Cell Lines - Osman Coşkun; Azranur Dumlu; Ayşe Neva Coşkun; Mustafa Emir Hacımüftüoğlu; Hilal Özbek; Fatma Yesilyurt (Atatürk University, 2024)
Anticancer Potential of Watermelon Seed Extracts Against Lung and Breast Cancer Cell LinesKarpuz Çekirdeği Ekstrelerinin Akciğer ve Meme Kanseri Hücre Hatlarına Karşı Antikanser PotansiyeliRunning Title: Anticancer Potential of Watermelon SeedAbstractObjective: The aim of the study is to evaluate the anticancer potential of watermelon seed extracts against lung and breast cancer cell lines. Methods: A549 lung cancer and MCF-7 breast cancer cell lines were used. The cells were treated with doses ranging from 0.1 to 1000 µg/mL of KI and KD extracts from watermelon seeds, starting when the cell density reached 80%. Viability was assessed using the MTT assay.Results: For the A549 lung cell line, the KI extract demonstrated significant anticancer activity at doses of 10, 100, and 1000 µg/mL, with the 1000 µg/mL dose being the most effective against lung cancer cells. Similarly, the KD extract showed efficacy across all doses tested, with the seed peel being effective at lower doses compared to the seed. In the MCF-7 breast cell line, both KI and KD extracts exhibited dose-dependent anticancer effects, with significant reductions in viability observed at all doses compared to the control group. Conclusion: Interestingly, the seed and seed shell showed selective effectiveness against breast and lung cancer, indicating a dose-dependent and selective anticancer effect. Overall, these findings suggest the potential of watermelon seed extracts as promising anticancer agents with selective efficacy against different cancer types. Keywords: Watermelon, anticancer, A549 lung cancer cell, MCF-7 breast cancer cellÖZAmaç: Çalışmanın amacı, karpuz çekirdeği ekstrelerinin akciğer ve meme kanseri hücre hatlarına karşı antikanser potansiyelini değerlendirmektir.Yöntemler: A549 akciğer kanseri ve MCF-7 meme kanseri hücre hatları kullanılmıştır. Hücreler, yoğunlukları %80'e ulaştığında, karpuz çekirdeğinden hazırlanan KI ve KD ekstreleri ile 0.1 ila 1000 µg/mL doz aralığında muamele edilmiştir. Canlılık, MTT testi kullanılarak değerlendirilmiştir.Bulgular: A549 akciğer hücre hattı için KI ekstresi, 10, 100 ve 1000 µg/mL dozlarında önemli antikanser aktivite göstermiş, 1000 µg/mL dozu akciğer kanseri hücrelerine karşı en etkili olarak bulunmuştur. Benzer şekilde, KD ekstresi, test edilen tüm dozlarda etkili olmuş ve tohum kabuğunun, tohuma göre daha düşük dozlarda etkili olduğu görülmüştür. MCF-7 meme hücre hattında, hem KI hem de KD ekstreleri doza bağlı antikanser etki sergilemiş ve kontrol grubuna kıyasla tüm dozlarda önemli düzeyde canlılık azalması gözlenmiştir.Sonuç: Karpuz çekirdeği ve kabuğu meme ve akciğer kanserine karşı seçici etkinlik göstermiş, bu da doza bağlı ve seçici bir antikanser etkiyi işaret etmektedir. Genel olarak, bu bulgular, karpuz çekirdeği ekstrelerinin farklı kanser türlerine karşı seçici etkili ve umut vaat edici antikanser ajanlar olarak potansiyelini göstermektedir.Anahtar kelimeler: Karpuz, antikanser, A549 akciğer kanseri hücre, MCF-7 meme kanseri hücre